A chiral magnetic molybdenum disulfide nanocomposite for direct enantioseparation of RS-propranolol. Issue 8 (9th February 2023) - Yu, Hai-Rong; Lei, Li; Wang, Yan-Lin; Wang, Xi; Liang, Ting; Cheng, Chang-Jing
Abstract : A novel chiral magnetic MoS2 nanocomposite with high enantioselectivity and excellent thermosensitivity and magnetism is developed for enantioseparation of RS -propranolol. Abstract : We herein report a novel chiral magnetic molybdenum disulfide nanocomposite (MMoS2 /PNG-CD) with a high enantioselectivity and excellent thermosensitivity and magnetism. The prepared MMoS2 /PNG-CD shows temperature-dependent chiral discrimination and enantioselectivity toward a chiral drug RS -propranolol ( RS -PPL), which is based on the molecular recognition ability of beta-cyclodextrin (β-CD) and the thermosensitivity of poly( N -isopropylacrylamide) (PNIPAM). The synthesized MMoS2 /PNG2-CD by using a monomer molar ratio of GMA to NIPAM of 2 : 1 demonstrates a high selectivity toward R -PPL over S -PPL due to the synergistic effect of the PNIPAM moieties and β-CD hosts. The thermo-induced volume phase transition (VPT) of the introduced PNIPAM moieties significantly affects the inclusion constants of the β-CD/ R -PPL complex, and thus the loading and desorption of R -PPL on the MMoS2 /PNG2-CD. The enantioselectivity at temperatures below the lower critical solution temperature (LCST) of the PNG-β-CD grafting chains is much higher than that at temperatures above the LCST. As a result, the regeneration of the MMoS2 /PNG2-CD is easily achieved via simply changing the operating temperature. Moreover, the regenerated MMoS2 /PNG2-CD can be readily recovered from the RS -PPL solution under an external magnetic field for reuse. Such a multifunctional molybdenum disulfide nanocomposite with a high enantioselectivity and excellent thermosensitivity and regenerability is promising to serve as a high-performance nanoselector for direct resolution of various β-blocker drugs.